Advisory opinion of the international court of justice in the “wall case” in the service of a possible solution of the Israeli-Palestinian conflict - Ganić Senad (Međunarodni Problemi)
The Arab-Israeli conflict even today represents one of the most complex problems facing the international community. The biggest controversy of the problem lies in the conflicting interpretations of the reasons offered by both sides. The way to overcome this impasse, is precisely the way recourse to international institutions. For this reason, the surprising fact is, that one very important decision of The International Court of Justice, it seems, remained unjustly neglected, especially if we take into account the importance of the issues which the Court dealt and the beneficial impact that this decision may have in the process of resolving the conflict in the Middle East. We believe that Advisory Opinion on Legal Consequences of the Construction of a Wall in the Occupied Palestinian Territory hides the way to a possible solution of this exhausting conflict. To consider because it comes to a legal analysis of the situation, which was given by the authorities in whose objectivity we supposed not to suspect as we supposed not to doubt on the objectivity of international law. Therefore, we consider it important to once again remind the decision, believing that in this way we can help to better understand the nature of this conflict, but also the reasons which indicate its possible peaceful solution.